2022
DOI: 10.1111/beer.12467
|View full text |Cite
|
Sign up to set email alerts
|

Women on boards and corporate environmental performance in Italian companies: The importance of nomination background

Abstract: In recent years, environmental protection and the green revolution have been at the top of the political agenda of many countries, especially those with female leaders. In Europe, for example, Ursula von Leiden and Christina Lagard are determined to pursue the green transition to meet the climate change mitigation goals. In the United States, in an interview with Forbes magazine, U.S. Representative Barbara Lee said, "Women understand the importance of compassion, communication and reason. They bring a perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…However, considering the most recent studies on diversity, sustainability, and corporate responsibility, the results are inconclusive. Thus, several studies have found a positive relationship (i.e., Al‐Najjar & Salama, 2022; Beji et al, 2020; De Masi et al, 2022; Elmagrhi et al, 2019; Galletta et al, 2022; García‐Sánchez et al, 2023; Govindan et al, 2021; Issa et al, 2022; Moreno‐Ureba et al, 2022; Provasi & Harasheh, 2020; Rehman et al, 2020; Shoham et al, 2017; Uyar et al, 2021; Wang et al, 2022; Yaseen et al, 2019), while others have observed non‐significant (Ardito et al, 2020; Ajaz et al, 2020; Zaid et al, 2020) and even negative (Bristy et al, 2020; Fakir & Jusoh, 2020; Garcia‐Sanchez, Gallego‐Alvarez, & Zafra‐Gomez, 2021; Loukil et al, 2019; Orazalin & Baydauletov, 2020; Sanan, 2016) relationships, presenting divergences in favor of economic dimensions over social and environmental ones (Nadeem et al, 2020; Nguyen et al, 2021). In addition, there may be a temporary effect that indicates changes in the role that female directors play, in the sense that a change has been observed in the interest they show regarding the adoption of ethical policies and management of the firm's activities (i.e., Monteiro et al, 2021; Nadeem et al, 2017), something that did not occur in previous times (i.e., García‐Sánchez et al 2015; Rodriguez‐Dominguez et al, 2009).…”
Section: Female Directors Social Identity and Incidental Affect: Rese...mentioning
confidence: 99%
“…However, considering the most recent studies on diversity, sustainability, and corporate responsibility, the results are inconclusive. Thus, several studies have found a positive relationship (i.e., Al‐Najjar & Salama, 2022; Beji et al, 2020; De Masi et al, 2022; Elmagrhi et al, 2019; Galletta et al, 2022; García‐Sánchez et al, 2023; Govindan et al, 2021; Issa et al, 2022; Moreno‐Ureba et al, 2022; Provasi & Harasheh, 2020; Rehman et al, 2020; Shoham et al, 2017; Uyar et al, 2021; Wang et al, 2022; Yaseen et al, 2019), while others have observed non‐significant (Ardito et al, 2020; Ajaz et al, 2020; Zaid et al, 2020) and even negative (Bristy et al, 2020; Fakir & Jusoh, 2020; Garcia‐Sanchez, Gallego‐Alvarez, & Zafra‐Gomez, 2021; Loukil et al, 2019; Orazalin & Baydauletov, 2020; Sanan, 2016) relationships, presenting divergences in favor of economic dimensions over social and environmental ones (Nadeem et al, 2020; Nguyen et al, 2021). In addition, there may be a temporary effect that indicates changes in the role that female directors play, in the sense that a change has been observed in the interest they show regarding the adoption of ethical policies and management of the firm's activities (i.e., Monteiro et al, 2021; Nadeem et al, 2017), something that did not occur in previous times (i.e., García‐Sánchez et al 2015; Rodriguez‐Dominguez et al, 2009).…”
Section: Female Directors Social Identity and Incidental Affect: Rese...mentioning
confidence: 99%
“…Indeed, according to the agency and the RBV logic, family firms' specific behavior can affect their reporting practices differently. Second, we contribute to the stream on gender diversity in family firms (Campopiano et al, 2019;Martinez Jimenez, 2009;Rovelli et al, 2022) by showing that gender-diverse boards shape family firms' dynamics and behaviors impacting firm outcomes including CSR reporting and ED (Campopiano et al, 2019;De Masi et al, 2022;Samara et al, 2019).…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 92%
“…Rodrigue et al (2013) by noting the evidence to support the latter viewpoint, which suggests that firm governance structures play a symbolic as opposed to a strategic role in disclosing environmental concerns. More recently, various studies have produced mixed results regarding the relationship between a firm governance structures and its carbon disclosures (Bui et al, 2020; De Masi et al, 2022; Gerged, 2021; Karim et al, 2021; Orazalin, 2019; Palea & Drogo, 2020; Velte et al, 2020). Therefore, the current paper contributes to the literature by exploring the relationship of firm governance structures and carbon disclosures in high‐polluting firms.…”
Section: Introductionmentioning
confidence: 99%